Nodular scleroderma in a patient with chronic hepatitis C virus infection: A coexistent or causal infection? - Chayada Kokpol (2018)
Copyright © Cutis 2015. Nodular scleroderma is a rare form of scleroderma that may occur systemically or locally. The pathogenesis of this variant is unknown. We report the case of a 63-year-old woman with systemic scleroderma and chronic hepatitis C virus (HCV) infection who had numerous papules and nodules on the neck and trunk. Skin biopsies from her lesions revealed characteristic findings of scleroderma. This case not only depicts the rare entity of nodular scleroderma but demonstrates the association of HCV infection with systemic autoimmune diseases such as scleroderma.